6x+7+3=x+5

Simple and best practice solution for 6x+7+3=x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6x+7+3=x+5 equation:



6x+7+3=x+5
We move all terms to the left:
6x+7+3-(x+5)=0
We add all the numbers together, and all the variables
6x-(x+5)+10=0
We get rid of parentheses
6x-x-5+10=0
We add all the numbers together, and all the variables
5x+5=0
We move all terms containing x to the left, all other terms to the right
5x=-5
x=-5/5
x=-1

See similar equations:

| 1.5+20=2(x-16) | | 22x-35=16x-98 | | 8y-3y+2y-2y-2y=9 | | z−4=5 | | -41=z-42 | | 3z+6+z=3+3z+3 | | X+1=36-4x | | -4+2y=-19 | | 6m-5=23-4 | | 7x+9=4x-18 | | 5x+13=3(x+4)+2x+4 | | t4=3.71 | | 8z+3z-11z+3z=3 | | 7)x+4.9)=56 | | 18=6/5u | | 2q=12.28 | | 9(y-86)=36 | | 3c+7-c=-2c+23 | | 20=12+x | | 6p-15=5p | | 9x+80=8x(x+10) | | 5p=6p−15 | | k-k+3k=6 | | 7=k3+6 | | 4w=19.6 | | 4u-3u+4u=53 | | b3=4.2 | | 3b=74 | | -15+2x=14+13x | | 2b=41 | | z-19=95 | | 19v-9v=10 |

Equations solver categories